Transalveolar Extractions in Different Age Groups - Vivek.D.Menon1 , M R Muthusekhar2 , Dinesh Prabu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
To evaluate the prevalence of difficult extractions in different age groups. A retrospective study was donein an institutional setting. The data was retrieved from the college’s patient records. All the patients whounderwent transalveolar extractions were included in this study at a given time frame from june 2019 tomarch 2020. The patients’ age, gender and method of extraction were retrieved and tabulated. The data wasthen analyzed using a software (SPSS). A total of 291 patients were involved in this study,majority of thepatients belonged to the 31-40 years age group, 160 patients being male and the remaining 131 being femalepatients. Most difficult tooth which was commonly encountered during extraction was lower mandibularthird molars. Lower third molars are one of the most difficult teeth to be extracted, an increased number ofcases were seen in the 31-40 years age group, hence a better approach and skill to be trained in extractinglower third molars can be done in order to avoid further complications.